Nurturing Self-Esteem: Understanding the Role of Parenting Styles - Safi Dakhil Nawam; Ali Sabry Al-Yasari; Walaa Yehya Abed Zead (Kufa Journal for Nursing Sciences)
Background: The New research thoroughly examines the intricate and challenging role of foster parents, which involves various stressors beyond the usual challenges of parenthood. The study explores the connection between parenting style and self-esteem to determine the relationship.